Citra Perempuan dalam Novel Mirah Karya Elisabeth Ika: Kritik Sastra Feminis - Ayyazy, Haura Ghatza Zarqa; Israhayu, Eko Sri (Ruang Kata, 2025)
This research aims to describe the image of women in the novel Mirah by Elisabeth Ika. The image of women in this novel is interesting to be used as an object of study because this novel raises realistic women's problems with social life. The image of women in this novel is studied using a feminist literary criticism approach with the theory of feminism proposed by Sugihastuti. The theory contains several aspects, namely, physical aspects, psychological aspects, family aspects, and community aspects. This research was conducted using descriptive analysis method with literature review through data in the form of quotations in conversations, paragraphs and characters' thoughts that can define the image of women in the main character in the novel Mirah by Elisabeth Ika. The data source used in this research is the novel Mirah by Elisabeth Ika. Data collection techniques in this study used reading and note-taking techniques, while data analysis techniques used data reduction, data presentation and conclusion drawing. The result of this research is four aspects of women's image, namely (1) women's image in physical aspect, (2) women's image in psychological aspect, (3) women's image in family aspect, (4) women's image in society aspect